Implementation rates of uro‐oncology multidisciplinary meeting decisions. (14th September 2017) - Kinnear, Ned; Smith, Riley; Hennessey, Derek B.; Bolton, Damien; Sengupta, Shomik
Abstract : Objectives: To assess implementation rates of the consensus plans made at the uro‐oncology multidisciplinary meeting (MDM) of an Australian tertiary centre, and analyse obstacles to implementation. Methods: A retrospective review was performed of all patients discussed at the uro‐oncology MDM at our institution between 1 January and 30 June 2015. Rates of referral for MDM discussion after a new histological diagnosis of malignancy, categorised by tumour type, were assessed. Patient records were interrogated to confirm MDM plan implementation, with the outcomes examined being completion of MDM plan within 3 months and factors preventing implementation. Results: During the enrolment period, from 291 uro‐oncological procedures, 240 yielded malignant histology of which 160 (67%) were discussed at the MDM. Overall, 202 patients, including 32 females, were discussed at the uro‐oncology MDM. MDM consensus plans were implemented in 184 (91.1%) patients. Reasons for deviation from the MDM plan included delay in care, patient deterioration or comorbidities, patient preference, consultant decision, loss to follow‐up, and change in patient scenario due to additional new information. Conclusion: The MDM is increasingly important in the care of uro‐oncology patients, with about two‐thirds of new diagnoses currently captured. There appear to be few barriers to the implementation of consensus plans, with nearly all patients undergoing the recommended management.